PROFILE OF PATIENTS WITH CARPAL TUNNEL SYNDROME TREATED AT A REFERRAL SERVICE - PAIVA, HENVER RIBEIRO DE (Acta Ortop Bras, 2020)
OBJECTIVE: To describe the clinical and epidemiological characteristics of people diagnosed with carpal tunnel syndrome (CTS) treated at a hand surgery outpatient clinic of a regional referral service. METHODS: Interview and specific medical examination of 150 people diagnosed with CTS underwent, and statistical analysis of the results obtained. RESULTS: Women smokers, in the fifth decade of life, married, overweight and educated until the elementary level prevailed in our study. Arterial hypertension and diabetes were the most reported comorbidities, and Durkan’s test was the most prevalent. CONCLUSION: CTS is prevalent in women in their fifth decade of life, with bilateral involvement and high school. The hypertension and diabetes are the most common diseases in people with CTS. Level of evidence IV, Case series.